SYNTHESIS AND CRYSTAL STRUCTURE ANALYSIS OF 3 - (4 - METHOXYBENZYL) - 2, 3 – DIHYDRO - 4H – CHROMAN – 4 - ONE - Lalitha Simon; S. Shalini; C. R. Girija; K.K. Srinivasan; T.V. Venkatesha (European Scientific Journal, ESJ, 2013)
3-(4-methoxybenzyl)-2,3-dihydro-4H-chroman-4-one(C17H16 O3) was synthesized by refluxing 2'-Hydroxydihydrochalcone dissolved in ethanol with paraformaldehyde and 50% aqueous diethylamine. The compound is characterized by IR,1HNMR, MS and X-ray diffraction studies. The X-ray structure analysis indicates that the crystal suffers from the positional disorder over two positions, atomC1 and C9 with required site occupancies of 0.590 and 0.410 leading to a conformational difference between the major and minor components. After applying similarity restraints, the final reliability index is 0.0275 for 2209 unique reflections .The crystal packing is stabilized by inter molecular C-H…O, C-H…π and π …π interactions.